EKSPLORASI MAKSIM KESANTUNAN BERBAHASA DALAM CHAT GRUP WA KELUARGA BESAR IKATAN MAHASISWA MUHAMMADIYAH UNVERSITAS HALU OLEO: TINJAUAN PRAGMATIK - Gege, Muhammad Yazid Abd. Rachim; Jumaidi, Jumaidi (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
This research aims to explore language politeness maxims in the Whatsapp Group chat of the Muhammadiyah Student Association of Halu Oleo University. The method used is descriptive qualitative by describing the chat speech of the Halu Oleo University Muhammadiyah Student Association's extended family chat group, the data of which was collected through screenshots in the group. The data was analyzed in 4 stages, namely 1) identifying the data, 2) classifying the data based on its form, 3) describing what had been previously classified, 4) analyzing the data, and 5) concluding the data. The results of the research show that the politeness maxims in the Whatsapp group chat of the Muhammadiyah Student Association of Halu Oleo University fulfill Leech's principles of the maxim of wisdom (6 data), the principle of the maxim of generosity (3 data), the principle of the maxim of respect (6 data), the principle of the maxim of humility heart (4 data), the principle of the maxim of consensus (8 data), the principle of the maxim of sympathy (5 data).